2016
DOI: 10.1371/journal.pone.0168078
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-497 Inhibits Cardiac Hypertrophy by Targeting Sirt4

Abstract: Cardiac hypertrophy is an adaptive enlargement of the myocardium in response to overload pressure of heart. From abundant studies, a conclusion is drawn that many microRNAs (miRNAs) are associated with cardiac hypertrophy and heart failure. To investigate the role of microRNA-497 (miR-497) in myocardial hypertrophy, two models were established in this study from cell level to integral level. Cardiac hypertrophy was induced by using angiotensin Ⅱ (Ang Ⅱ) in vitro and was created by transverse abdominal aortic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
(20 reference statements)
4
28
0
Order By: Relevance
“…Thus, it provides new evidences to explore the functions of miRNAs in modulating mitochondrial function. For instance, miR‐106a accelerates cardiac hypertrophy via restraining mitofusin 2, miR‐497 and miR‐485‐5p attenuate cardiac hypertrophy by targeting Sirt4 and MAPL, respectively . In present study, we found that miRNA‐miR‐376b‐3p negatively regulate mitochondrial fission in cardiac hypertrophic NRVCs by targeting MFF.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Thus, it provides new evidences to explore the functions of miRNAs in modulating mitochondrial function. For instance, miR‐106a accelerates cardiac hypertrophy via restraining mitofusin 2, miR‐497 and miR‐485‐5p attenuate cardiac hypertrophy by targeting Sirt4 and MAPL, respectively . In present study, we found that miRNA‐miR‐376b‐3p negatively regulate mitochondrial fission in cardiac hypertrophic NRVCs by targeting MFF.…”
Section: Discussionsupporting
confidence: 55%
“…For instance, miR-106a accelerates cardiac hypertrophy via restraining mitofusin 2, 30 miR-497 and miR-485-5p attenuate cardiac hypertrophy by targeting Sirt4 and MAPL, respectively. 26,31 In present study, we found that miRNA-miR-376b-3p negatively regulate mitochondrial fission in cardiac hypertrophic NRVCs by targeting MFF. miR-376b plays major roles in regulating of various biology activities including cancer, 32,33 liver regeneration, 34 angiogenesis 35 and cardioprotection.…”
Section: Discussionsupporting
confidence: 53%
“…Only later, a link between activation of the fetal gene program, miRNAs, and HF development was suggested [160][161][162]. For some solitary miRNAs, a role in pathological cardiac remodeling in animal models was found [160,[163][164][165][166]. Also, in humans, the relationship between miRNAs and cardiac remodeling has been investigated.…”
Section: Looking Beyond Circulating Proteins: Micrornas and Metabolitmentioning
confidence: 99%
“…This study (65) demonstrated that SIRT4 overexpression increased oxidative stress by inhibiting SIRT3 binding and deacetylation of manganese SOD, an important mediator in scavenging ROS. In addition, suppression of SIRT4 by miRNA-497 overexpression diminished the adverse hypertrophic response induced by transverse aortic constriction in mice (106). Furthermore, knockdown of SIRT4 was shown to improve metabolic functions by upregulating FAO metabolism in myocytes and hepatocytes, further suggesting that SIRT4 may be detrimental to the heart (48,72).…”
Section: Biosynthesis and Metabolism Of Nad ϩmentioning
confidence: 98%